BARBARA-CHRISTINE NENTWIG SILVA: PATHWAYS OF DEDICATION AND COMMITMENT TO GEOGRAPHY - Maina Pirajá; Silvana Sá de (GeoNordeste, 2018)
The objective of this research is to describe the trajectory of commitment and dedication to the Geography of the teacher and researcher PhD. Barbara-Christine Nentwig Silva. This is one of the most important working geographers in Bahia and one of the most influential researchers of theoretical-quantitative Geography in Brazil. From the methodological point of view, they used the open questionnaire research with the teacher and analysis of their curriculum lattes, as well as historical and comparative revisions of some of their intellectual productions, and testimonials and thanks in thesis and dissertations of some of his former students. Thus, the results showed that for almost five decades, Professor Barbara-Christine has been leaving a legacy of teachings and knowledge for Geography, which serves as an inspiration for present and future geographers.